Energy efficiency through lighting systems in institutional buildings in Nigeria - Abdullahi, Abdurrahman Yusuf; Hj Mohd Ariffin, Noor Aziah; Ibrahim, Illyani (EM International, 2017)
Energy for lighting consumes about 12% of the world demand. All buildings including universities consume a significant amount of lighting energy but have the most potential in reducing lighting energy consumption. This research was aimed at exploring the use of lighting technology as a way of improving energy efficiency at the Agriculture Faculty Building (AFB), Kano University of Science and Technology (KUST), Wudil in Kano, Nigeria. Three lighting systems: the commonly used T8 fluorescent (FLT8), and the improved T5 fluorescent (FLT5) and light-emitting diode tubular (LED) were experimented to identify which of them would be the most suitable for improving energy efficiency. The methodology involved calculations to determine the energy consumption of the different lamps used. Secondly, the return on investment was obtained by using simple payback period and lastly the GHG reduction savings was calculated to investigate which lighting has the least impact on the environment. The findings from this study showed that the FLT5 and LED lamps saved more energy as compared to the FLT8. The FLT5 and LED projected savings of more than 40% and better reduction of the CO2 emission by more than 2 metric tons. FLT5 lamps have a better return on investment (ROI) in thirty years, and the study indicated that FLT5 is a more efficient choice in the long run.